Sustainability knowledge and behaviors of apparel and textile undergraduates - Hiller Connell, Kim Y.; Kozar, Joy M. (My University, 2012)
Purpose – The purpose of this paper is to analyze changes in undergraduate student knowledge of issues of sustainability relevant to the apparel and textiles industry. Assessment occurred prior to and upon completion of a course that addressed topics specific to the global production and distribution of apparel and textile goods. The study also examined modifications in students’ reported apparel purchasing behaviors. Design/methodology/approach – Participants included those in their third, fourth or fifth year of undergraduate education in the apparel and textile discipline at a higher education institution located in the Midwestern USA. All participants were enrolled in a course focused on globalization and the apparel and textile industry. Measures used to assess students’ knowledge of social and environmental sustainability issues related to the industry and their apparel purchasing behavior were included in the research instrument. Findings – Pre and post comparisons revealed significant changes in students’ knowledge of social and environmental issues relevant to the apparel and textile industry. However, the study found no significant adjustments in apparel purchasing behavior. Further, a post hoc analysis revealed no significant relationship between students’ knowledge and their reported purchasing behavior. Originality/value – Limited resources exist which examine methods for educating apparel and textile students about sustainability issues, with even less research documented on assessing the effectiveness of these methods. The paper analyzes the contributions sustainability-focused curriculum can make in modifying the level of knowledge and purchasing behavior of students and recommends further strategies to yield possibly even greater results.
Keywords: Apparel purchasing behavior; Apparel sustainability; Sustainability knowledge